Genome‐wide association analysis identifies a GLUL haplotype for familial hepatitis B virus‐related hepatocellular carcinoma. Issue 20 (29th June 2017) - Lin, You‐Yu; Yu, Ming‐Whei; Lin, Shi‐Ming; Lee, Shou‐Dong; Chen, Chih‐Ling; Chen, Ding‐Shinn; Chen, Pei‐Jer
Abstract : BACKGROUND: A family history of liver cancer increases the risk of developing hepatocellular carcinoma (HCC) by 2‐fold to 10‐fold among patients with chronic hepatitis B virus (HBV). Previous genome‐wide association studies have identified many possible susceptible loci associated with sporadic HBV‐related HCC. However, despite family history being a well‐known risk factor for HBV‐related HCC, to the authors' knowledge its genetic mechanisms and associating loci remain largely unknown or unexplored, most likely due to the relative rarity of familial HCC and the difficulty of sample collection. METHODS: The authors conducted a genome‐wide association study with 139 male cases with familial HBV‐related HCC and 139 non‐HCC male controls with chronic HBV. The results were corroborated further with an independent cohort of 101 patients with familial HBV‐related HCC and comparison with both the 1000 Genomes Project and the Taiwan Biobank. RESULTS: A total of 51 risk single‐nucleotide polymorphisms ( P ≤1E‐04) were identified in the association analyses, which included 2 clusters of associated single‐nucleotide polymorphisms and haplotypes at 1q25.3 (glutamate‐ammonia ligase [ GLUL ]/transmembrane epididymal protein 1 [ TEDDM1 ]/long intergenic non‐protein‐coding RNA 272 [ LINC00272 ]/regulator of G‐protein signaling‐like 1 [ RGSL1 ]) and 17q11.2 (solute carrier family 13 member 2 [ SLC13A2 ]/forkhead box N1 [ FOXN1 ]). Both the GLUL and SLC13A2 / FOXN1 haplotypes have large effect sizes and were found to be different from those found from genome‐wide association studies of sporadic HCCs. CONCLUSIONS: To the authors' knowledge, the current study is the first genome‐wide association study to identify genetic factors for familial HBV‐related HCC. The results identified 2 large effect susceptible haplotypes located at GLUL and SLC13A2 / FOXN1 . The current study findings also suggest different genetic susceptibility between familial and sporadic HBV‐related HCC. Cancer 2017;123:3966‐76 . © 2017 American Cancer Society . Abstract : In the current study, genome‐wide association analyses were performed to identify genetic factors associated with familial hepatitis B virus‐related hepatocellular carcinoma. The results identified 2 familial hepatocellular carcinoma‐specific susceptible haplotypes at glutamate‐ammonia ligase ( GLUL ) and solute carrier family 13 member 2 ( SLC13A2 )/forkhead box N1 ( FOXN1 ).